Clinical Perspective on 2019 Novel Coronavirus Pneumonia: A Systematic Review of Published Case Reports - Patel, Rikinkumar S (Cureus, 2020)
The ongoing pandemic of 2019 novel coronavirus (2019-nCoV), which originated from Wuhan, China, has led to 68,279 deaths due to 2019-nCoV pneumonia as of May 5, 2020. We conducted a systematic review and included 16 case reports to summarize the transmission and pathology of 2019-nCoV, and clinical presentation, laboratory and imaging findings, and treatment in 2019-nCoV pneumonia. The disease is mild in most people; in some, it may progress to severe pneumonia with acute respiratory distress syndrome (ARDS). Patients with mild illness usually recover at home, with supportive care and isolation in accordance with guidelines. Patients who have moderate to severe pneumonia are usually monitored in the hospital. Although there is no definitive treatment for 2019-nCoV pneumonia so far, some antiviral drugs have shown promising results. The use of lopinavir/ritonavir and remdesivir was associated with significant clinical improvement in severe pneumonia. Nonetheless, we need more randomized clinical trials (RCTs) and treatment guidelines for developing effective management of the 2019-nCoV and improve patient outcomes by reducing mortality in high-risk patients. We also need ﻿more clinical trials and management guidelines for the effective management of 2019-nCoV pneumonia.